Embryology Theory and Practice - Wu, Bin; Feng, Huai L. (IntechOpen, 2019)
Recently developed new embryology theory may greatly improve the success of assisted reproductive technology (ART) in the treatment of human infertility and animal well-being. This book updates and reviews newly developed theories and technologies in human in vitro fertilization and focuses mainly on discussing its clinical practice. Areas covered include ovarian stimulation medicine and final ART outcomes, involving oocyte in vitro maturation, oocyte fertilization and failure treatment, blastocyst formation and implantation, as well as regulation of neuroendocrine embryo implantation. Thus, this book will add new knowledge for readers to improve their appreciation of ART.